2016
DOI: 10.1371/journal.pone.0159399
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine Palmitoyltransferase 1 Increases Lipolysis, UCP1 Protein Expression and Mitochondrial Activity in Brown Adipocytes

Abstract: The discovery of active brown adipose tissue (BAT) in adult humans and the fact that it is reduced in obese and diabetic patients have put a spotlight on this tissue as a key player in obesity-induced metabolic disorders. BAT regulates energy expenditure through thermogenesis; therefore, harnessing its thermogenic fat-burning power is an attractive therapeutic approach. We aimed to enhance BAT thermogenesis by increasing its fatty acid oxidation (FAO) rate. Thus, we expressed carnitine palmitoyltransferase 1AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…The adipocytes depended heavily on FA oxidation when stimulated with isoproterenol. Numerous studies support the notion that modulation of the mitochondrial FA carriers affects FA oxidation and thermogenesis in brown adipocytes (7,8,21,25), underlining the important role of FAs not only as substrates but also as activators of thermogenesis (9). Respiration also depended heavily on glucose oxidation, although the glucose pathway flexibility was very low in ISO-treated cells.…”
Section: Discussionmentioning
confidence: 79%
“…The adipocytes depended heavily on FA oxidation when stimulated with isoproterenol. Numerous studies support the notion that modulation of the mitochondrial FA carriers affects FA oxidation and thermogenesis in brown adipocytes (7,8,21,25), underlining the important role of FAs not only as substrates but also as activators of thermogenesis (9). Respiration also depended heavily on glucose oxidation, although the glucose pathway flexibility was very low in ISO-treated cells.…”
Section: Discussionmentioning
confidence: 79%
“…fetal serum, 1% (vol./vol.) penicillin/streptomycin (Sigma-Aldrich) and 2 mmol/l HEPES, and differentiated until they exhibited numerous multilocular cytoplasmic lipid droplets [26]. Undifferentiated (day 0) pre-adipocytes were treated with 0.1 μg/ml PTN (Sigma-Aldrich) until day 6 of differentiation; at this time point, non-treated pre-adipocytes typically achieved a fully differentiated phenotype.…”
Section: Cell Culture and Differentiation Of Brown Adipocytesmentioning
confidence: 99%
“…According to all these algorithms, our results show that the three most stable genes were Hprt1, Tbp, and Rpl32 for IBAT and Tbp, B2m, and Hprt1 for RWAT, while the least stable genes were 18S, Actb, and Gapdh for both tissues. The Actb and Gapdh genes are widely used in the literature as normalizers for the evaluation of target gene expression in WAT and BAT (Aguirre et al, 2016;Antony et al, 2017;Calderon-Dominguez et al, 2016;Chang and Kim, 2017;Li et al, 2015;Rodrigues et al, 2017;Tsubai et al, 2016;Yan et al, 2017), however, a few authors argue about the stability of the reference genes. A systematic review showed that the vast majority of the studies use a single gene as a normalizer, with Actb and/or Gapdh being commonly selected to evaluate the gene expression in vertebrates (Chapman and Waldenstrom, 2015).…”
Section: Discussionmentioning
confidence: 99%